The Potential of Plant-Derived Extracts and Compounds to Augment Anticancer Effects of Chemotherapeutic Drugs. (13th August 2022) - Ng, Chu Xin; Affendi, Muzaira Mazrul; Chong, Pei Pei; Lee, Sau Har
Abstract: Plant extracts comprise a complex mixture of natural compounds with diverse biological activities including anticancer activities. This has made the use of plant extracts a trending strategy in cancer treatment. In addition, plants' active constituents such as polyphenols could confer protective effects on normal cells against damage by free radicals as well as lessen the toxicity of chemotherapeutic drugs. Recently, many emerging studies revealed the combinatory uses of plant extracts and individual therapeutic compounds that could be a promising panacea in hampering multiple signaling pathways involved in cancer development and progression. Besides enhancing the therapeutic efficacy, this has also been proven to reduce the dosage of chemotherapeutic drugs used, and hence overcome multiple drug resistance and minimize treatment side effects. Notably, combined use of plant extracts with chemotherapeutics drugs was shown to enhance anticancer effects through modulating various signaling pathways, such as P13K/AKT, NF-κB, JNK, ERK, WNT/β-catenin, and many more. Hence, this review aims to comprehensively summarize both In Vitro and In Vivo mechanisms of actions of well-studied plant extracts, such as Ganoderma Lucidum, Korean red ginseng, Garcinia sp., curcumin, and luteolin extracts in augmenting anticancer properties of the conventional chemotherapeutic drugs from an extensive literature search of recent publications.